Comparison of permanent deformation and fatigue resistance of hot mix asphalts prepared with the same performance grade binders - Alataş, Taner; Yılmaz, Mehmet; Kök, Baha Vural; Koral, Aykut Fatih (My University, 2012)
In this study, the volumetric properties, Marshall stabilities, the indirect tensile stiffness moduli, and the fatigue and permanent deformation strengths of hot mix asphalts prepared with the same performance grade binders in accordance with Superpave method at optimum binder contents were comparatively investigated. In addition, the effect of bitumen modi?cation using SBS on the mechanical characteristics of the mixtures was evaluated. Dynamic creep and indirect tensile fatigue tests were conducted at two distinct stress levels and three different loading periods. As the binder tests, it was determined that the modi?ed bitumen obtained by adding of 3% SBS by weight into the B 160/220 binder yielded the same level of performance with the B 70/100 bitumen. It was also found that using 3% SBS by weight for the purpose of bitumen modi?cation enhanced the desired properties of the mixture to a signi?cant degree. It was observed that the best performance belonged to the mixtures containing B 70/100 bitumen, while the worst performance was found for the mixtures made from B 160/220 bitumen. Additionally, although the mixtures prepared by the same performance grade binders in accordance with the Superpave system were expected to behave similarly, it was found that they differed considerably with respect to their stiffness, tensile strength and strength against permanent deformation.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hot mix asphalt; Superpave; Performance grade; Fatigue; Permanent deformation